High-purity light metal doped LiNbO3 piezoelectric coating and preparation method thereof
By doping light metal elements in lithium niobate targets, the problems of Li deficiency and impurity phase in LiNbO3 piezoelectric coating are solved, and piezoelectric coatings with high purity and excellent performance are obtained, especially in ultrasonic signals and high temperature stability. Excellent sexual performance.
Patent Information
- Application Number
- CN202411632487.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The low atomic weight of the Li element causes the LiNbO3 piezoelectric coating to easily scatter during magnetron sputtering, resulting in Li deficiency phenomenon and the formation of impurity phases, affecting the purity and performance of the coating.
Doping light metal elements such as Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, Y in the target, the lithium niobate piezoelectric coating is deposited through magnetron sputtering technology to adjust the doping Elements and their contents are used to obtain a high-purity LiNbO3 piezoelectric coating to avoid the formation of lithium deficiency phase and impurity phase.
The preparation of high-purity LiNbO3 piezoelectric coating is realized, which improves the piezoelectric constant and ultrasonic signal performance of the coating, and shows excellent high-temperature performance stability.
Smart Images

Figure CN119144930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium niobate piezoelectric coatings, in particular to high-purity light metal-doped LiNbO 3 Method for preparing piezoelectric coating. Background Art
[0002] Among the ultrasonic sensors commonly used in the industrial field, lithium niobate (LiNbO 3 ) is a commonly used coating material for preparing piezoelectric thin films. At present, magnetron sputtering technology is generally used to prepare lithium niobate into a piezoelectric coating and coat it on the substrate. Magnetron sputtering refers to the process in which electrons collide with argon atoms in the process of flying to the substrate under the action of an electric field, causing them to ionize and produce Ar positive ions and new electrons; under the action of the electric field, new electrons fly to the substrate, and Ar positive ions fly to the cathode target and bombard the target surface with high energy, causing the target material to sputter. Among the sputtered particles, neutral target atoms or molecules are deposited on the substrate to form a thin film.
[0003] However, the low atomic weight of Li element gives LiNbO 3 The sputtering growth of piezoelectric coatings brings great problems. Due to the short mean free path, some Li atoms are easily scattered in the gas mixture and diffuse to the walls of the deposition chamber of the magnetron sputtering equipment instead of being transferred to the substrate. In order to solve the above problems, the deposition of non-stoichiometric lithium niobate films has been reported in the literature. Maintaining a low substrate temperature can weaken the Li deficiency phenomenon. Combined with sputtering parameters such as gas pressure and RF power, it is beneficial to reduce the lithium-deficient phase (such as LiNb 3 O 8 ), lithium-rich phase (such as Li 3 NbO 4 ) formation, improving the LiNbO 3 purity. Summary of the invention
[0004] The present invention provides a high-purity light metal doped LiNbO 3 Piezoelectric coating and preparation method thereof, by doping certain light metal elements in the target material, so that the prepared lithium niobate piezoelectric coating does not contain LiNb 3 O 8 Lack of lithium phase, and no NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating: By adjusting the doping elements and their contents, a piezoelectric constant and ultrasonic signal superior to those of pure lithium niobate coating can be obtained. The technical solution of the present invention is specifically implemented by the following technologies.
[0005] The present invention provides a high-purity light metal doped LiNbO 3 The method for preparing a piezoelectric coating comprises the following steps:
[0006] Designing a light metal element doped lithium niobate target, wherein the light metal refers to a metal located before Nb in the periodic table, and generally at least one of Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, and Y can be selected;
[0007] Polishing and cleaning substrates and magnetron sputtering equipment;
[0008] When a stainless steel substrate is used, a natural oxide layer will form on the surface of the substrate, which will affect the bonding performance between the coating and the substrate, reduce the conductivity of the substrate and the bracket, and destroy the uniformity of the bias voltage. Therefore, in some implementation cases, it is necessary to use 600-1500 mesh sandpaper to grind the front and back of the stainless steel substrate;
[0009] In order to fully remove the surface dirt of the magnetron sputtering equipment and improve the conductivity, in some implementation cases, a grinder and 600-1000 mesh sandpaper are used to grind the key components of the magnetron sputtering equipment, such as the substrate holder, stainless steel sheet, support seat, target fixing ring and bolts.
[0010] Installing the light metal element-doped lithium niobate target and substrate in the magnetron sputtering equipment;
[0011] The specific installation method is that the target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate bracket by a stainless steel sheet. At the same time, in order to facilitate the subsequent cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated so that the front side of the substrate (i.e., the surface for depositing and coating the lithium niobate piezoelectric coating) and the surface of the light metal element doped lithium niobate target are in a non-relative state;
[0012] Start the magnetron sputtering equipment (turn on mechanical pumps, molecular pumps, heaters and other components) until the ideal vacuum degree and target temperature are reached;
[0013] Rotating the front side of the substrate to a non-opposite state with the surface of the light metal element-doped lithium niobate target, setting environmental parameters, and cleaning the surface of the light metal element-doped lithium niobate target;
[0014] The front side of the substrate is rotated to face the surface of the light metal element doped lithium niobate target material, environmental parameters are set, and a radio frequency magnetron sputtering method is used to deposit the light metal element doped lithium niobate piezoelectric coating on the front side of the substrate;
[0015] Setting environmental parameters includes introducing Ar gas and O 2 The gas is supplied and the flow rate is controlled, and the RF power and bias voltage are set.
[0016] The high-purity light metal-doped LiNbO 3In the preparation method of piezoelectric coating, the substrate is not limited in size and material range, and experimental substrate or industrial substrate can be selected. Among them, the experimental substrate can be selected from single crystal silicon wafers or stainless steel sheets, which are used to characterize the surface morphology, cross-sectional morphology, film thickness, crystal structure, elemental composition and other information of the coating, providing a reference for industrial applications. Industrial substrates are mainly bolts, which are used to measure ultrasonic signals and test the piezoelectric properties and high-temperature stability of the coating.
[0017] Furthermore, based on the atomic mass of the light metal, the number of doped atoms of the light metal accounts for 0.25-8.5%.
[0018] Furthermore, when the light metal is Cr, the number of doped atoms accounts for 1.1-6.42%.
[0019] Furthermore, when the light metal is Sc, the amount of doping atoms accounts for 1.4-3.0%.
[0020] Furthermore, when the light metal is Zr, the number of doped atoms accounts for 1.01-3.34%.
[0021] Furthermore, when the light metal is Cu, the number of doped atoms accounts for 0.86-6.72%.
[0022] Furthermore, when the light metal is Zn, the amount of doped atoms accounts for 1.83-3.81%.
[0023] Furthermore, when the light metal is Fe, the number of doped atoms accounts for 2.1-4.83%.
[0024] Furthermore, when the light metal is Ti, the amount of doped atoms accounts for 0.27-1.4%.
[0025] Furthermore, when the light metal is Ni, the number of doped atoms accounts for 0.55-5.11%.
[0026] Furthermore, when the light metal is Al, the amount of doping atoms accounts for 0.7-1.25%.
[0027] Furthermore, when the light metal is Co, the number of doped atoms accounts for 5.2-8.3%.
[0028] Furthermore, when the light metal is Y, the number of doping atoms accounts for 1.60-5.03%.
[0029] Furthermore, the ideal vacuum degree is (1 – 5)×10 -3 Pa.
[0030] Furthermore, the target temperature for heating the magnetron sputtering device may be selected to be 100-200°C.
[0031] Furthermore, in the environmental parameters, the Ar gas and O 2 The volume ratio of the gas flow rate is 4 / 1-6 / 1, Ar gas and O 2 The total gas flow rate is 0.9-2.0 Pa.
[0032] Furthermore, in the setting of environmental parameters, the RF power is 800-900 W and the bias voltage is 2-10 V.
[0033] Furthermore, the distance between the front surface of the substrate and the surface of the light metal element-doped lithium niobate target is 4.5-7 cm.
[0034] Furthermore, the surface cleaning time of the light metal element doped lithium niobate target is 6-12 min.
[0035] Further, light metal doped LiNbO is deposited 3 The time for piezoelectric coating is 6-9 h.
[0036] In some embodiments of the present invention, the light metal doped LiNbO 3 The target material preparation method is as follows:
[0037] As needed, add Nb in a molar ratio of 1:1 2 O 5 and Li 2 Add light metal to the mixed raw material, mix thoroughly in a ball mill for 5-10 hours to form a uniform raw material; sieve, weigh, and mold to make a cylindrical light metal-doped target with a diameter of 14.7-19.7 cm and a thickness of 4.1-5.1 mm;
[0038] The light metal doped target is annealed to reduce the hardness of the target, improve the uniformity of grain size and length, and facilitate obtaining a higher target sputtering rate. The specific annealing method is to first treat at 900℃ for 60 minutes and then at 1100℃ for 2 hours;
[0039] After the target material is cooled naturally, the surface and outer circle are stripped and processed, and a copper backing plate (15-20cm in diameter and 3.1-4.1mm in thickness) with a diameter slightly larger than the target material is bonded with high-temperature resistant glue, and then cleaned and dried to form the required light metal-doped lithium niobate target material.
[0040] By observing the microscopic morphology and crystal structure of lithium niobate piezoelectric coatings doped with the above light metals, it can be seen that these coatings have excellent columnar crystal structures and do not contain lithium-deficient phase LiNb 3 O 8, and does not contain NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating has fine spherical grains and columnar crystal structure.
[0041] The present invention also provides high-purity light metal-doped LiNbO prepared by the above preparation method. 3 Piezoelectric coating.
[0042] Compared with the prior art, the present invention is beneficial in that: the present invention prepares light metal-doped LiNbO by doping several specific metals in the target material of magnetron sputtering. 3 The microscopic morphology of the piezoelectric coating was observed to have good spherical and columnar crystal structures and did not contain lithium-deficient phase LiNb. 3 O 8 , and does not contain NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating. By adjusting the doping elements and their content, the piezoelectric constant and ultrasonic signal can be obtained that are superior to those of pure lithium niobate coatings. 3 Piezoelectric coatings have excellent high temperature performance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the crystal structure of the Zr-doped lithium niobate piezoelectric coating of Experimental Example 1.
[0044] Figure 2 This is the surface morphology of the lithium niobate piezoelectric coating in Experimental Example 1 with the Zr-doped atoms accounting for 1.59%.
[0045] Figure 3 This is the crystal structure of the Zn-doped lithium niobate piezoelectric coating of Experimental Example 2.
[0046] Figure 4 This is the surface morphology of the lithium niobate piezoelectric coating in Experimental Example 2, in which the number of Zn-doped atoms accounts for 2.49%.
[0047] Figure 5 Ultrasonic signals (ultrasonic intensity, V) of the lithium niobate piezoelectric coating in which the number of Zn-doped atoms accounts for 2.49% of Experimental Example 2 and the pure lithium niobate piezoelectric coating of the comparative example.
[0048] Figure 6 Ultrasonic signal (longitudinal wave intensity, V) and piezoelectric constant (pC / N) of the Zn-doped lithium niobate piezoelectric coating of Experimental Example 2.
[0049] Figure 7This is the crystal structure of the Ti-doped lithium niobate piezoelectric coating of Experimental Example 3.
[0050] Figure 8 The surface and cross-sectional morphologies of the lithium niobate piezoelectric coating in Experimental Example 3, in which the number of Ti-doped atoms accounts for 0.68%.
[0051] Fig. 9 Ultrasonic signals (ultrasonic intensity, V) of the lithium niobate piezoelectric coating with Ti doping amount of 0.68% in Experimental Example 3 and the pure lithium niobate piezoelectric coating in the comparative example.
[0052] Fig.10 are the ultrasonic signal (longitudinal wave intensity, V) and piezoelectric constant (pC / N) of the Ti-doped lithium niobate piezoelectric coating of Experimental Example 3, where Fig.10 (a) is the data before annealing. Fig.10 (b) in the figure is the data after high temperature annealing at 700℃ for 5h.
[0053] Fig.11 This is the crystal structure of the Al-doped lithium niobate piezoelectric coating of Experimental Example 4.
[0054] Fig.12 This is the surface morphology of the lithium niobate piezoelectric coating in Experimental Example 4, in which the number of Al-doped atoms accounts for 0.99%. DETAILED DESCRIPTION
[0055] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] The high-purity light metal doped LiNbO 3 The method for preparing a piezoelectric coating comprises the following steps:
[0057] (1) Design a lithium niobate target doped with a light metal, wherein the light metal is at least one of Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, and Y.
[0058] (2) Cleaning substrate and magnetron sputtering equipment:
[0059] ① Substrate deoxidation treatment: For stainless steel substrates, since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 600-1500 mesh sandpaper to polish the surface and back of the stainless steel to be coated;
[0060] ② Use a grinder and 600-1000 mesh sandpaper to grind the substrate holder, stainless steel sheet, support seat, target fixing ring and bolts to fully remove surface dirt and improve conductivity.
[0061] (3) The target material and substrate are installed in the magnetron sputtering equipment: the target material is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. At the same time, in order to facilitate the subsequent cleaning of the target material surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target material in a non-relative state.
[0062] (3) Turn on the mechanical pump, molecular pump, heater and other magnetron sputtering equipment components, and evacuate the equipment to the ideal vacuum degree (1 – 5)×10 -3 Pa, and heated to the target temperature of 100-200°C;
[0063] (4) Cleaning the target surface: Introducing Ar and O 2 , Ar / O 2 The ratio is between 4 / 1 and 6 / 1, the total flow rate is between 0.9 Pa and 2.0 Pa, the RF power is between 800 and 900 W, the bias voltage is between 2 and 10 V, and the target cleaning time is 5 to 15 min.
[0064] (5) After the target is cleaned, a light-element-doped lithium niobate piezoelectric coating is deposited by radio frequency magnetron sputtering: the substrate is rotated so that its front side is opposite to the target surface with a spacing of 4.5 cm to 7 cm, and the light-element-doped lithium niobate coating is deposited. Ar and O are introduced. 2 , Ar / O 2 The ratio of the deposition rate is between 4 / 1 and 6 / 1, the total flow rate is between 0.9 Pa and 2.0 Pa, the RF power is between 800 and 900 W, the bias voltage is between 2 and 10 V, and the deposition time is between 6 and 9 h.
[0065] The structure, morphology, elements, ultrasonic properties and piezoelectric properties of the above-mentioned light metal-doped lithium niobate coating were tested.
[0066] In some implementation cases, based on the atomic mass of the light metal, the amount of doping atoms of the light metal accounts for 0.25-8.5%.
[0067] Specifically, when the light metal is Cr, the number of doped atoms accounts for 1.1-6.42%.
[0068] When the light metal is Sc, the amount of doping atoms accounts for 1.4-3.0%.
[0069] When the light metal is Zr, the number of doped atoms accounts for 1.01-3.34%.
[0070] When the light metal is Cu, the number of doped atoms accounts for 0.86-6.72%.
[0071] When the light metal is Zn, the number of doped atoms accounts for 1.83-3.81%.
[0072] When the light metal is Fe, the number of doped atoms accounts for 2.1-4.83%.
[0073] When the light metal is Ti, the amount of doping atoms accounts for 0.27-1.4%.
[0074] When the light metal is Ni, the number of doped atoms accounts for 0.55-5.11%.
[0075] When the light metal is Al, the amount of doping atoms accounts for 0.7-1.25%.
[0076] When the light metal is Co, the number of doped atoms accounts for 5.2-8.3%.
[0077] When the light metal is Y, the number of doping atoms accounts for 1.60-5.03%.
[0078] In some embodiments of the present invention, light metal doped LiNbO 3 The target material preparation method can be selected as follows:
[0079] (1) Add Nb with a molar ratio of 1:1 as needed 2 O 5 and Li 2 Add light metal to the mixed raw material, mix thoroughly in a ball mill for 5-10 hours to form a uniform raw material; sieve, weigh, and mold to make a cylindrical light metal-doped target with a diameter of 14.7-19.7 cm and a thickness of 4.1-5.1 mm;
[0080] (2) Annealing treatment is performed on the light metal doped target to reduce the hardness of the target, improve the uniformity of grain size and length, and facilitate obtaining a higher sputtering rate. The specific annealing treatment method is to first treat at 900°C for 60 minutes and then at 1100°C for 2 hours;
[0081] (3) After the target material is cooled naturally, the surface and outer circle are stripped and bonded with a copper backing plate (15-20 cm in diameter and 3.1-4.1 mm in thickness) with a diameter slightly larger than the target material using high temperature resistant glue, and then cleaned and dried to form the required light metal doped lithium niobate target material.
[0082] In the following four test examples of the present invention, pure lithium niobate target (without any metal element or any other substance doped) was selected as a control to prepare pure lithium niobate piezoelectric coating. The method for preparing the target (deposition steps and equipment parameters, etc.) is basically the same as the method for preparing the target doped with light metal, the only difference being that light metal or other substances are not doped in step (1). After testing, the ultrasonic signal of the formed pure lithium niobate piezoelectric coating before annealing is 0.45V, and the piezoelectric constant d 33 is 2.6 pC / N, the ultrasonic signal is 1.2V after high temperature annealing at 700℃ for 5h, and the piezoelectric constant d 33 It is 4.6 pC / N (ultrasonic performance test parameters are: transmitting voltage 100 V, gain 40 dB).
[0083] Experimental Example 1: Effect of the proportion of Zr doping atoms on the performance of high-purity light metal-doped LiNbO 3 Effect of piezoelectric coating on performance
[0084] The high-purity light metal-doped LiNbO provided in this test example 3 The method for preparing a piezoelectric coating comprises the following steps:
[0085] (1) Design of Zr-doped lithium niobate target.
[0086] Three lithium niobate targets are designed, and their basic components are all composed of Nb 2 O 5 , Li 2 O, and also contains ZrO, with Zr atomic contents of 1.24%, 1.59% and 2.42% respectively;
[0087] The preparation method of the target material in this test example is:
[0088] ① According to the above Zr atomic content requirements, the molar ratio of Nb 2 O 5 and Li 2 ZrO is added to the mixed raw material of O, and the raw material is put into a ball mill and mixed thoroughly for 6 h. The uniform raw material is sieved, weighed, and molded to make a cylindrical Zr metal-doped target with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0089] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0090] ③ After the target material is cooled naturally, the flat surface and outer circle are demolded, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, cleaned and dried to form the required Zr-doped lithium niobate target material.
[0091] (2) Polishing and cleaning substrates and magnetron sputtering equipment.
[0092] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0093] ② Use a grinder and 800-grit sandpaper to grind key components such as the substrate holder, stainless steel sheet, support seat, target fixing ring and bolts used in the magnetron sputtering equipment in turn to fully remove surface dirt and improve conductivity.
[0094] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0095] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, temperature is 150℃ environment.
[0096] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power to 900 W, the bias voltage to 7 V, and the target cleaning for 10 min.
[0097] (6) Three lithium niobate piezoelectric coatings with different Zr doping contents were deposited by magnetron sputtering: After cleaning, the substrate was rotated so that its front side was opposite to the target surface with a spacing of 5.3 cm, and the Zr-doped lithium niobate coating was deposited: Ar, O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power between 900 W, the bias voltage between 7 V, and the deposition time 8 h to obtain a lithium niobate piezoelectric coating deposited on the substrate surface.
[0098] (7) Carry out structural, morphological and elemental tests on the obtained Zr-doped lithium niobate piezoelectric coating.
[0099] The structure, morphology and element test results of Experimental Example 1 are shown in Figure 1-2 As shown, Figure 1 is the relevant crystal structure, Figure 2 The surface morphology of the lithium niobate piezoelectric coating with a Zr atomic content of 1.59%. Figure 1 and2 It can be seen that the lithium niobate piezoelectric coatings with three different Zr doping atomic ratios do not contain LiNb 3 O 8 Lack of lithium phase, and no NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating has fine spherical grains and columnar crystal structure.
[0100] Experimental Example 2: Effect of the proportion of Zn doping atoms on the performance of high-purity light metal-doped LiNbO 3 Effect of piezoelectric coating on performance
[0101] The high-purity light metal-doped LiNbO provided in this test example 3 The method for preparing a piezoelectric coating comprises the following steps:
[0102] (1) Design of Zn-doped lithium niobate target:
[0103] Three lithium niobate targets are designed, and their basic components are all composed of Nb 2 O 5 , Li 2 O composition, in addition to ZnO, the Zn atomic content is 2.06%, 2.49% and 3.62% respectively;
[0104] The preparation method of the target material in this test example is:
[0105] ① According to the above Zn atomic content requirements, the molar ratio of Nb 2 O 5 and Li 2 ZnO is added to the mixed raw material, which is put into a ball mill and mixed thoroughly for 6 h. The uniform raw material is sieved, weighed, and molded to produce a cylindrical Zn metal-doped target with a diameter of 14.7 cm and a thickness of 4.2 mm.
[0106] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0107] ③ After the target material is cooled naturally, the surface and outer circle are demolded, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, and then cleaned and dried to form the required Zn-doped lithium niobate target material.
[0108] (2) Polishing and cleaning substrates and magnetron sputtering equipment.
[0109] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0110] ② Use a grinder and 800-grit sandpaper to grind the key components of the magnetron sputtering equipment, such as the sample holder, stainless steel sheet, support seat, target fixing ring and bolts, to fully remove surface dirt and improve conductivity.
[0111] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0112] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, temperature is 150℃ environment.
[0113] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power to 900 W, the bias voltage to 7 V, and the target cleaning for 10 min.
[0114] (6) Three lithium niobate piezoelectric coatings with different Zn doping contents were deposited by magnetron sputtering: After cleaning, the substrate was rotated so that its front side was opposite to the target surface with a spacing of 5.3 cm, and the Zn-doped lithium niobate coating was deposited: Ar, O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power between 900 W, the bias voltage between 7 V, and the deposition time 8 h to obtain a lithium niobate piezoelectric coating deposited on the substrate surface.
[0115] (7) The obtained Zn-doped lithium niobate piezoelectric coating was tested for structure, morphology, elements, ultrasonic properties (ultrasonic performance test parameters were emission voltage 100 V, gain 40 dB) and piezoelectric properties.
[0116] The structure, morphology and element test results of Experimental Example 2 are shown in Figure 3 and 4 As shown, Figure 3 is the relevant crystal structure, Figure 4The surface morphology of the lithium niobate piezoelectric coating with a Zn atomic content of 2.49%. Figure 3 and 4 It can be seen that the lithium niobate piezoelectric coatings with three different Zn doping atomic ratios do not contain LiNb 3 O 8 Lack of lithium phase, and no NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating has fine spherical grains and columnar crystal structure.
[0117] The ultrasonic performance and piezoelectric performance test results of Experimental Example 2 are as follows: Figure 5 and 6 As shown in the figure, the piezoelectric constants d of lithium niobate piezoelectric coatings with Zn atomic contents of 2.06%, 2.49% and 3.62% were measured. 33 They are 3.75 pC / N, 3.90 pC / N and 3.05 pC / N respectively. It can be seen that the ultrasonic signals and piezoelectric constants of the three Zn-doped lithium niobate piezoelectric coatings with different doping atomic content are stronger than those of the pure lithium niobate piezoelectric coating, and the Zn-doped lithium niobate piezoelectric coating with a Zn atomic content of 2.49% has the strongest ultrasonic signal and piezoelectric constant.
[0118] Experimental Example 3: Effect of the ratio of Ti doping atoms on the performance of high purity LiNbO 3 Effect of piezoelectric coating on performance
[0119] The high-purity LiNbO 3 The method for preparing a piezoelectric coating comprises the following steps:
[0120] (1) Design of Ti-doped lithium niobate target:
[0121] Three lithium niobate targets are designed, and their basic components are all composed of Nb 2 O 5 and Li 2 O composition, and also contains TiO 2 , the Ti atomic contents are 0.41%, 0.68% and 1.40% respectively;
[0122] The preparation method of the target material in this test example is:
[0123] ① According to the above Ti atomic content requirements, the molar ratio of Nb 2 O 5 and Li 2 O mixed raw materials with TiO 2 , put it into a ball mill and mix it thoroughly for 6 h, then sieve, weigh and mold the uniform raw material to make a cylindrical Ti metal-doped target with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0124] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0125] ③ After the target material is cooled naturally, the surface and outer circle are stripped and processed, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, cleaned and dried to form the required Ti-doped lithium niobate target material.
[0126] (2) Polish and clean the substrate and magnetron sputtering equipment. Magnetron sputtering was used to deposit three lithium niobate piezoelectric coatings with different Zn doping contents:
[0127] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0128] ② Use a grinder and 800-grit sandpaper to grind the key components of the magnetron sputtering equipment, such as the sample holder, stainless steel sheet, support seat, target fixing ring and bolts, to fully remove surface dirt and improve conductivity.
[0129] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0130] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, environment with temperature of 150℃;
[0131] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power to 900 W, the bias voltage to 7 V, and the target cleaning for 10 min.
[0132] (6) Three lithium niobate piezoelectric coatings with different Ti doping contents were deposited by magnetron sputtering: After cleaning, the substrate was rotated so that its front side was opposite to the target surface with a spacing of 5.3 cm, and Ti-doped lithium niobate coatings were deposited: Ar, O 2 , Ar / O 26 / 1, total flow rate 2.0 Pa, and set the RF power between 900 W, the bias voltage between 7 V, and the deposition time 8 h to obtain a lithium niobate piezoelectric coating deposited on the substrate surface.
[0133] (7) The obtained Ti-doped lithium niobate piezoelectric coating was subjected to structural, morphological, elemental, ultrasonic performance (ultrasonic performance test parameters are: emission voltage 100 V, gain 40 dB), and piezoelectric performance tests.
[0134] (8) The obtained Ti-doped lithium niobate piezoelectric coating was subjected to a high-temperature annealing experiment at 700°C for 5 h, and then the acoustic performance (ultrasonic performance test parameters are: emission voltage 100 V, gain 40 dB) and piezoelectric performance tests were carried out to verify the performance stability.
[0135] The structure, morphology and element test results of Experimental Example 3 are as follows: Figure 7 and 8 As shown, Figure 7 is the relevant crystal structure, Figure 8 The surface morphology of lithium niobate piezoelectric coating with a Ti atomic content of 0.68%. Figure 7 and 8 It can be seen that the lithium niobate piezoelectric coatings with three different proportions of Ti doped atoms do not contain LiNb 3 O 8 Lack of lithium phase, and no NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating has fine spherical grains and columnar crystal structure.
[0136] The ultrasonic performance and piezoelectric performance test results of Experimental Example 3 before annealing are as follows: Fig. 9 and Fig.10 As shown in (a), the piezoelectric constants d of lithium niobate piezoelectric coatings with Ti atomic contents of 0.41%, 0.68% and 1.40% were measured. 33 They are 3.55 pC / N, 4.45 pC / N and 3.15 pC / N respectively. It can be seen that the ultrasonic signals and piezoelectric constants of the three Ti-doped lithium niobate piezoelectric coatings with different doping atomic content are stronger than those of the pure lithium niobate piezoelectric coating, and the Ti-doped lithium niobate piezoelectric coating with a Ti atomic content of 0.68% has the strongest ultrasonic signal and piezoelectric constant.
[0137] The ultrasonic and piezoelectric properties test results of Experimental Example 3 after annealing at 700°C for 5h are as follows: Fig.10 As shown in (b), the piezoelectric constants d of lithium niobate piezoelectric coatings with Ti atomic contents of 0.41%, 0.68% and 1.40% are 33, ultrasonic signals are still stronger than those of pure lithium niobate piezoelectric coatings, and the Ti-doped lithium niobate piezoelectric coating with a Ti atomic content of 0.68% has the strongest ultrasonic signal and piezoelectric constant. At the same time, compared with the data before annealing, the piezoelectric constant d of the Ti-doped lithium niobate piezoelectric coating after high-temperature annealing at 700℃ for 5h is 33 , and ultrasonic signals are greatly improved, indicating that the Ti-doped lithium niobate piezoelectric coating has excellent high-temperature performance stability.
[0138] Example 4: Effect of the ratio of Al doping atoms on the performance of high purity light metal doped LiNbO 3 Effect of piezoelectric coating on performance
[0139] The high-purity light metal-doped LiNbO provided in this test example 3 The method for preparing a piezoelectric coating comprises the following steps:
[0140] (1) Design of Al-doped lithium niobate target:
[0141] Three lithium niobate targets are designed, and their basic components are all composed of Nb 2 O 5 and Li 2 O composition, and also contains Al 2 O 3 , the Al atomic contents are 0.73%, 0.99% and 1.25% respectively;
[0142] The preparation method of the target material in this test example is:
[0143] ① According to the above Al atomic content requirements, Nb 2 O 5 and Li 2 O mixed raw material doped with Al 2 O 3 , put it into a ball mill and mix it thoroughly for 6 hours, sieve the uniform raw material, weigh it, and mold it to make a cylindrical Al metal-doped target with a diameter of 14.7 cm and a thickness of 4.2 mm;
[0144] ② Annealing treatment was performed at 900℃ for 60 min and 1100℃ for 2h in sequence;
[0145] ③ After the target material is cooled naturally, the surface and outer circle are demolded, and a copper back plate with a diameter of 15 cm and a thickness of 3.2 mm is bound with high-temperature resistant glue, and then cleaned and dried to form the required Al-doped lithium niobate target material.
[0146] (2) Polishing and cleaning substrates and magnetron sputtering equipment.
[0147] ① Substrate deoxidation treatment: stainless steel substrate is selected; since a natural oxide layer will form on the surface of the substrate, which affects the bonding performance between the coating and the substrate, reduces the conductivity of the substrate and the bracket, and destroys the uniformity of the bias voltage, it is necessary to use 1200-grit sandpaper to polish the surface and back of the stainless steel to be coated;
[0148] ② Use a grinder and 800-grit sandpaper to grind the key components of the magnetron sputtering equipment, such as the sample holder, stainless steel sheet, support seat, target fixing ring and bolts, to fully remove surface dirt and improve conductivity.
[0149] (3) Installing the target and substrate in the magnetron sputtering device: The target is fixed by a fixing ring and bolts, and the substrate is suspended on the substrate holder by a stainless steel sheet. In order to facilitate the cleaning of the target surface without contaminating the substrate, the support seat needs to be rotated to set the front side of the substrate (i.e., the surface for depositing the lithium niobate piezoelectric coating) and the surface of the target in a non-relative state.
[0150] (4) Turn on the mechanical pump, molecular pump, and heater to create a vacuum degree of 3.2×10 -3 Pa, temperature is 150℃ environment.
[0151] (5) Cleaning the target surface: Rotate the substrate so that its back side is opposite to the target surface to clean the target surface; introduce Ar and O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power to 900 W, the bias voltage to 7 V, and the target cleaning for 10 min.
[0152] (6) Three lithium niobate piezoelectric coatings with different Al doping contents were deposited by magnetron sputtering: After cleaning, the substrate was rotated so that its front side was opposite to the target surface with a spacing of 5.3 cm, and the Al-doped lithium niobate coating was deposited: Ar, O 2 , Ar / O 2 6 / 1, total flow rate 2.0 Pa, and set the RF power between 900 W, the bias voltage between 7 V, and the deposition time 8 h to obtain a lithium niobate piezoelectric coating deposited on the substrate surface.
[0153] (7) Carry out structural, morphological and elemental tests on the obtained Al-doped lithium niobate piezoelectric coating.
[0154] The test results of Example 4 are as follows Fig.11 and 12 As shown, Fig.11 is the relevant crystal structure, Fig.12 The surface morphology of the lithium niobate piezoelectric coating with an Al atomic content of 0.99%. Fig.11 and 12It can be seen that the lithium niobate piezoelectric coatings with three different Al doping atomic ratios do not contain LiNb 3 O 8 Lack of lithium phase, and no NbO, Nb 2 O 5 etc. impurity phase, high-purity LiNbO 3 Piezoelectric coating has fine spherical grains and columnar crystal structure.
[0155] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating, characterized in that: The following steps are involved: Design light metal element doped lithium niobate targets; Polishing and cleaning substrates and magnetron sputtering equipment; Installing the light metal element-doped lithium niobate target and substrate in the magnetron sputtering equipment; Start the magnetron sputtering equipment until the ideal vacuum degree and target temperature are reached; Rotating the front side of the substrate to a non-opposite state with the surface of the light metal element-doped lithium niobate target, setting environmental parameters, and cleaning the surface of the light metal element-doped lithium niobate target; The front side of the substrate is rotated to face the surface of the light metal element doped lithium niobate target material, and environmental parameters are set to deposit the light metal element doped lithium niobate piezoelectric coating on the front side of the substrate by radio frequency magnetron sputtering; In the light metal element doped lithium niobate target, the light metal is at least one of Cr, Sc, Zr, Cu, Zn, Fe, Ti, Ni, Al, Co, and Y; Setting the environmental parameters includes introducing Ar gas and O2 gas and controlling the inflow flow rate, setting the RF power and bias voltage.
2. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: Based on the atomic mass of the light metal, the number of doped atoms of the light metal accounts for 0.25-8.5%.
3. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: When the light metal is Cr, the proportion of doping atoms is 1.1-6.42%; When the light metal is Sc, the proportion of doping atoms is 1.4-3.0%; When the light metal is Zr, the proportion of doping atoms is 1.01-3.34%; When the light metal is Cu, the proportion of doping atoms is 0.86-6.72%; When the light metal is Zn, the proportion of doping atoms is 1.83-3.81%; When the light metal is Fe, the proportion of doping atoms is 2.1-4.83%; When the light metal is Ti, the amount of doping atoms accounts for 0.27-1.4%; When the light metal is Ni, the proportion of doping atoms is 0.55-5.11%; When the light metal is Al, the proportion of doping atoms is 0.7-1.25%; When the light metal is Co, the proportion of doping atoms is 5.2-8.3%; When the light metal is Y, the number of doped atoms accounts for 1.60 – 5.03%.
4. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The ideal vacuum degree is (1 – 5)×10 -3 Pa.
5. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The target temperature for heating the magnetron sputtering device may be selected to be 100-200°C.
6. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: In setting the environmental parameters, the flow volume ratio of the introduced Ar gas and O2 gas is 4 / 1-6 / 1, and the total flow rate of Ar gas and O2 gas is 0.9-2.0Pa.
7. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: In the environmental parameter settings, the RF power is 800-900 W and the bias voltage is 2-10 V.
8. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The distance between the front side of the substrate and the surface of the light metal element-doped lithium niobate target is 4.5-7 cm.
9. The method for preparing a high-purity light metal-doped LiNbO3 piezoelectric coating according to claim 1, characterized in that: The deposition time of light metal doped LiNbO3 piezoelectric coating is 6-9 h.
10. A high-purity light metal-doped LiNbO3 piezoelectric coating prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium niobate piezoelectric coating with adjustable and controllable longitudinal and transverse sound waves as well as preparation method and application of lithium niobate piezoelectric coating
CN117467955A
Method for producing piezoelectric films with rotating magnetron sputtering system
EP1124270A2
Cited By
High-density LiNbO3 target material, preparation method, piezoelectric coating and application thereof
CN120398537B
High-titanium-doped lithium niobate target material, preparation method thereof and sensor
CN122079627A
